Health professionals' perspectives on information provision for patients with brain tumours and their families. Issue 2 (19th September 2012) - Langbecker, D.; Janda, M.; Yates, P.
<x xml:space="preserve">Abstract</x> LANGBECKER D., JANDA M. & YATES P. (2012) European Journal of Cancer Care22, 179–187 Health professionals' perspectives on information provision for patients with brain tumours and their families A significant number of patients diagnosed with primary brain tumours report unmet information needs. Using concept mapping methodology, this study aimed to identify strategies for improving information provision, and to describe factors that health professionals understood to influence their provision of information to patients with brain tumours and their families. Concept mapping is a mixed‐methods approach that uses statistical methods to represent participants' perceived relationships between elements as conceptual maps. These maps, and results of associated data collection and analyses, are used to extract concepts involved in information provision to these patients. Thirty health professionals working across a range of neuro‐oncology roles and settings participated in the concept mapping process. Participants rated a care coordinator as the most important strategy for improving brain tumour care, with psychological support as a whole rated as the most important element of care. Five major themes were identified as facilitating information provision: health professionals' communication skills, style and attitudes; patients' needs and preferences; perceptions of patients' need for protection and initiative; rapport and continuity between patients and health professionals; and the nature of the healthcare system. Overall, health professionals conceptualised information provision as 'individualised', dependent on these interconnected personal and environmental factors.